Accessibility of ART in the farming community of OR Tambo District Municipality in the Eastern Cape province - Lorraine N. Mntonintshi-Mketo; Phillip Nhlanhla (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: South Africa accounts for 14% of all new HIV infections representing the highest annual rate of new HIV infections globally. In addition, South Africa is home to 21% of the worldwide HIV burden, with 7.97 million people living with HIV. HIV not only affects the health of those living with the virus but also impacts their economic well-being.